IPO Underpricing and After-Market Liquidity - Ellul, Andrew; Pagano, Marco (Review of Financial Studies, 2006)
The underpricing of initial public offerings (IPOs) is generally explained with asymmetric information and risk. We complement these traditional explanations with a new theory where investors worry also about the after-market illiquidity that may result from asymmetric information after the IPO. The less liquid the aftermarket is expected to be, and the less predictable its liquidity, the larger will be the IPO underpricing. Our model blends such liquidity concerns with adverse selection and risk as motives for underpricing. The model’s predictions are supported by evidence for 337 British IPOs effected between 1998 and 2000. Using various measures of liquidity, we find that expected after-market liquidity and liquidity risk are important determinants of IPO underpricing.